STUDENTS’ PERCEPTION ON THE USE OF VLOG AS LEARNING MEDIA FOR EF SPEAKING SKILL - Nihta V. F. Liando; Samuel F. Lasut; Paula Rombepajung (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study is to find out students’ perceptions toward a learning media for EFL speaking skills. The purpose of this study is to find out students’ perceptions toward a learning media for EFL speaking skills. In this research, the researcher used questionnaires. The method of data analysis was descriptive method, which is analysing the data by illustrating the object of the research. The population of this research was the second-grade students of SMA Lokon St. Nikolaus Tomohon. There were 4 classes that spread into 2 science classes and 2 social classes. There were 107-second year students. And the sample was taken from science and social class based on the teacher’s recommendation. There were 35 students participating in this research to answer the questionnaires. Based on the results of this study, it was found that the students’ perception toward the statements was dominated positively because students were having a great experience in watching Video Blog. As conclusion, YouTube English Vlog was considered effective to the second-year students of SMA Lokon St. Nikolaus Tomohon. English teachers were suggested to always do something creative, follow the technology, and improve what needs to be improved for example blending the media with some interesting stimulations.